2022
DOI: 10.1101/2022.12.07.519423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Species and condition shape the mutational spectrum in experimentally evolved biofilms

Abstract: Laboratory experimental evolution provides a powerful tool for studying microbial adaptation to different environments. To understand the differences and similarities of the dynamic evolutionary landscapes of two model species from the Bacillus genus as they adapt to abiotic and biotic surfaces, we revived the archived population samples from our four previous experimental evolution studies and performed longitudinal whole-population genome sequencing. Surprisingly, higher number of mutations, higher genotypic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Here, we provide more evidence that IS can increase fitness and play an important role in adaptation, as was already shown across different species ranging from Enterobacteria (Consuegra et al 2021 , Frazão et al 2022 ) to Cyanobacteria (Miller et al 2021 ). A recent study in Bacillus subtilis and Bacillus thuringensis revived end-point populations from four different evolution experiments and showed that, independently of growth in either biotic or abiotic conditions, insertion sequences are critical in adaptation (Hu et al 2023 ). No differences were found across Bacillus species.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we provide more evidence that IS can increase fitness and play an important role in adaptation, as was already shown across different species ranging from Enterobacteria (Consuegra et al 2021 , Frazão et al 2022 ) to Cyanobacteria (Miller et al 2021 ). A recent study in Bacillus subtilis and Bacillus thuringensis revived end-point populations from four different evolution experiments and showed that, independently of growth in either biotic or abiotic conditions, insertion sequences are critical in adaptation (Hu et al 2023 ). No differences were found across Bacillus species.…”
Section: Discussionmentioning
confidence: 99%
“…To dissect the mutational landscapes of B. subtilis adapted in the presence or absence of A. niger, sequential populations of each lineage at each transfer were subjected to high-coverage metagenome sequencing (except the first three timepoints of four Bac lineages). Singlenucleotide polymorphisms (SNPs) and short insertions and deletions (indels) were determined using the breseq pipeline [29][30][31] which detected 142 and 157 mutations with >5% frequency in CoEvo and Bac populations, respectively (frequencies of each mutated gene in each lineage are shown in Supplementary Fig. 2a and the mutation types are shown in Supplementary Dataset 1).…”
Section: Mutation Of the Global Regulator Degu Enhances Spreading In ...mentioning
confidence: 99%